Perancangan Buku Fotografi Dokumentasi Panggung Musik Band Tani Maju - Didit Prasetyo Nugroho (LPPM STIKI Malang, 2024)
Malang City is one of the cities in Indonesia that has a rich and diverse music history. One of the famous music groups from Malang City is Tani Maju. Established since 1999, Tani Maju continues to enliven the music scene in Malang City until today. This research is a project by the author who has also been a documentation stage photographer for Tani Maju since 2009 until now. This research will result in a photography book documenting Tani Maju's music stage as the main medium. Music stage documentation photography is a branch of photography that focuses on documenting music performances. This photography book will contain photos of Tani Maju on stage, taken by the author from 2009 to mid-2019, and has undergone photography quality selection and editing processes by the author. The design method applied in this research is using a qualitative approach. The general aim of this design is to create a photography book that contains documentation of Tani Maju's music stage, and the benefits derived from this research and design are to add one form of visual artwork for the author and Tani Maju Band in the form of a music stage documentation book.